Dynamic interactions and diversification benefits between sukuk and bond markets : international evidence - Bhuiyan, Rubaiyat Ahsan (Kulliyyah of Economics and Management Sciences, International Islamic Universiy Malaysia, 2017)
There is an enormous impact of the financial subprime crisis on returns of many asset classes, questioning on the effectiveness of the portfolio theory. Post the global financial crisis, one of the major challenges for regulators and investors is to search for level of integration of financial markets in consideration that globalization and technological advancement have enhanced cross-class correlations and complicate diversification opportunities. This study attempts to examine empirically whether fixed income investors of developed and emerging countries can diversify their portfolio through investing in the global sukuk market. The first phase of the study which saw the reduction of the Value-at-Risk of hypothetical portfolios constructed with bond and sukuk indices, had motivated for further analysis be undertaken on the dynamic interaction between these two investment assets. In the second phase, this research investigates the co-movement and causality between sukuk and bond markets while in the last phase, it examines the diversification opportunities for global conventional fixed income investors through inclusion of sukuk in their portfolios. This study applies several approaches including wavelet analysis and DCC GARCH in examining the dynamic relations and diversification benefits of these two assets. In terms of data, the daily return of 14 bonds and sukuk indices covering the period from January 2010 to December 2015 are used. The findings suggest that Malaysian and global sukuk markets provide better diversification benefits for the developed and emerging market for fixed income investors. In addition to that, fixed income investors from developed countries could also gain higher diversification benefits compared to emerging market investors by considering both bond and sukuk in their portfolios. This research has demonstrated a deeper understanding of the characteristics of international sovereign bond markets from portfolio diversification perspective. Wavelet approach enriches the understanding of this dynamic behavior between sukuk and bond indices and it has significant implications for investors, regulators and portfolio managers. Information on cointegration and lead-lag relationship between sukuk and bond indices may also be useful for the regulators in terms of formulating macro stabilization policies for the countries as well as for fund managers in articulating their trading and investment activities.